Editorial (Condensed Matter Physics, 2013)
In this issue of the journal “Condensed Matter Physics” we publish a part of Proceedings of the 2nd
Ukrainian–Polish–Lithuanian Meeting on Ferroelectric Physics (UPL MFP-2). The meeting was held on
September, 9–13, 2012 in Lviv (Ukraine). It was organized by the Institute of Physical Optics of the Ministry
of Science, Youth and Sports of Ukraine.